Glucocorticoid receptor blockage and thymidine phosphorylase inhibition: a new treatment option for psoriasis - V., Aruna; Rajagopal, Gayathri; S., Ranganathan (International Journal of Research in Dermatology, 2025)
Background: The present study describes the efficacy of an ointment widely used in the treatment of psoriasis blocking glucocorticoid (GR) receptor in KU812 cells. Methods: The ointment is composed of various phyto-actives source from the botanicals such as Wrightia tinctoria, Cynodon dactylon, Boswellia serrata, and Hydnocarpus laurifolia. Results: The present findings clearly demonstrate the ointment having steroid-like effect essential for the treatment of psoriasis. The steroid like effect would hinder/reduce the inflammatory events, the major clinical manifestation in psoriasis. Further the ointment also has exhibited effect in inhibiting thymidine phosphorylase (TP) activity and thereby prevent/reduce the events that lead to angiogenesis and flow pro-inflammatory mediators at the site of lesion. Angiogenesis is one of the early changes that prelude inflammatory cascade. Conclusions: The dual efficacy of the ointment viz., blocking GR and inhibiting TP enzyme and thereby suppressing angiogenesis clearly indicate the essential therapeutic effect of the ointment for the treatment of psoriasis.